Computer algorithms in the field of wholesale power market : opportunities and challenges - Gasilina, Elvira (2022)
For a smooth transition from separate and independent state-managed power markets to a single interconnected decentralised Pan-European market, as an integral part of power market liberalisation process, the new power market coupling principle for electricity trading has recently become an important research topic. Due to the current decarbonisation framework, increasing the production of electricity from renewable sources leads to serious problems with network load imbalance. Unpredictable level of electricity production from renewable sources, the imbalance of both the demand and the supply of electricity, hardware constraints of generation from nuclear and conventional power plants, decentralisation of electricity flow management among the EU countries, and target of preserving system maximising social welfare creates a serious optimisation problem for efficient allocation of cross-border capacities in the transmission of electricity process and evaluation of spot prices in all market bidding zones. The efficient solution for the optimisation problem is the introduction of a single unified and more flexible system for trading of electricity between European countries. EUPHEMIA (Pan-European Hybrid Electricity Market Integration Algorithm) algorithm is a single price coupling algorithm, which allows for an automatic calculation of available cross-border capacities amongst EU regions, their efficient allocation to market participants in order to achieve maximum possible social welfare, and processing coupling of bids and asks of market participants, calculating electricity prices for coupled EU regions. This thesis attempts to assess opportunities and challenges of using EUPHEMIA computer algorithm in the field of wholesale power market by identifying and analysing impacts of an introduction of EUPHEMIA algorithm to the wholesale energy spot market.